A curious case of Lactococcus garvieae bacteremia associated with adenocarcinoma - Sam N. Amarasinghe; Andee L. Fontenot; Ammar Husan; Muhammad W. Khan (IDCases, 2022)
Lactococcus garvieae is a pathogen typically acquired from the consumption of raw seafood or unpasteurized dairy products. Here, we present the unique case of a middle-aged gentleman who presented with back pain, originally thought to be muscle spasms due to poor posture and heavy lifting. Initial radiological imaging showed evidence of a lumbar epidural abscess and lung nodule. Upon further work-up, L. garvieae was isolated in blood and abscess cultures. It was later hypothesized that the L. garvieae bacteremia might have an association with adenocarcinoma of the lung.